2021
DOI: 10.3390/ma14195839
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Water Adsorption Using Laser Photoacoustic Spectroscopy and Numerical Simulations

Abstract: In the present research we propose a model to assess the water vapors adsorption capacity of a SiO2 trap in the breathing circuit, aiming to reduce the loading of interfering compounds in human breath samples. In this study we used photoacoustic spectroscopy to analyze the SiO2 adsorption of interfering compounds from human breath and numerical simulations to study the flow of expired breath gas through porous media. As a result, the highest adsorption rate was achieved with a flow rate of 300 sccm, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…So, the study evaluated the carbon dioxide and ethylene gases found in human respiration before and after wearing a surgical face mask using the CO 2 laser photoacoustic spectroscopy method with respect to CO 2 laser frequencies [ 15 , 16 , 17 , 22 , 30 , 31 , 32 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…So, the study evaluated the carbon dioxide and ethylene gases found in human respiration before and after wearing a surgical face mask using the CO 2 laser photoacoustic spectroscopy method with respect to CO 2 laser frequencies [ 15 , 16 , 17 , 22 , 30 , 31 , 32 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The photoacoustic spectroscopy gas detection used for the evaluation of the carbon dioxide and ethylene is summarized in Figure 4 and described in detail in [ 15 , 16 , 17 , 22 , 30 , 31 , 32 , 41 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High sensitivities well below 1 ppb can be reached with gas chromatography techniques [7], but the measurements can be time consuming and the best performance often requires offline or offsite analysis with a separate sampling step [8]. Optical methods based on spectroscopic detection are an appealing alternative [9,10]. Optical spectrometers are often more compact and more readily develop into fieldcapable instruments and autonomous onsite detectors for continuous monitoring [11].…”
Section: Introductionmentioning
confidence: 99%